Apa Itu Roemah Kolaborasi? Sebuah Kelanjutan Kelas Menulis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Wahyudin Darmalaksana; Fitriani Fitriani; Susanti Vera; Hidayatul Fikra (Gunung Djati Conference Series, 2024)
This research aims to discuss the idea of establishing the Roemah Collaboration. This research is qualitative in nature by applying the Asset Based Community Development method. The results and discussions directed Roemah Collaboration to immediately prepare program offer proposals and recruit marketing resources whose role was to promote various activity programs to a wide audience. This research concludes that the idea of establishing Roemah Collaboration is considered appropriate in an effort to collect and combine various expertise competencies that work collaboratively to realize common goals.